CLINICAL STUDY OF PERIODONTAL PARAMETERS DURING THE ORTHODONTIC TREATMENT - Dorina-Cerasella Şincar; Răzvan Leaţă; Gabriel-Valeriu Popa; Mioara Decusară; Earar Kamel (Romanian Society of Oral Rehabilitation, 2018)
Introduction. Dento-maxillary abnormalities are an important factor affecting periodontal health, so one of the goals of orthodontic treatment is to promote better dental health and to prolong the life of the teeth. Orthodontic treatment contributes to improving oral hygiene by correcting dental irregularities and reducing (or eliminating) occlusal trauma. The placement of orthodontic appliances near the gingival sulcus, the accumulation of the plaque and the impediments they pose to the oral hygiene habits affect the periodontal health condition and complicate the orthodontic recovery process. Aim of the study. The purpose of this study was to clinically assess the evolution of the relationship between orthodontic therapy and gingival health. Material and methods. The study group comprised 31 patients with dento-maxillary abnormalities treated with orthodontic treatment. In 20 patients, was applied fixed orthodontic treatment and, at 11, functional mobile device. In these patients a periodontal clinical examination was performed at different times throughout the orthodontic therapy. Results. In this study, it was observed that plaque index values and those of gingival inflammation increased in all patients between baseline and end of treatment. These increases were statistically significant in patients treated with fixed orthodontic appliances. Also, in patients treated with functional devices have seen these parameters increase but after treatment they were not statistically significant. Conclusions. Regardless of the quality of bacterial plaque control, patients undergoing orthodontic treatment have an increased risk of developing generalized gingivitis in a very short time. In addition, the duration and type of orthodontic treatment significantly influence the development and development of this type of pathology.